2017
DOI: 10.1186/s13063-017-1795-9
|View full text |Cite
|
Sign up to set email alerts
|

The ACHRU-CPP versus usual care for older adults with type-2 diabetes and multiple chronic conditions and their family caregivers: study protocol for a randomized controlled trial

Abstract: BackgroundMany community-based self-management programs have been developed for older adults with type-2 diabetes mellitus (T2DM), bolstered by evidence from randomized controlled trials (RCTs) that T2DM can be prevented and managed through lifestyle modifications. However, the evidence for their effectiveness is contradictory and weakened by reliance on single-group designs and/or small samples. Additionally, older adults with multiple chronic conditions (MCC) are often excluded because of recruiting and rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 87 publications
0
15
0
1
Order By: Relevance
“…37 Finally, it enhances motivational skills for self-sufficiency, positive behaviours and independent attitudes towards disease. 3941…”
Section: Resultsmentioning
confidence: 99%
“…37 Finally, it enhances motivational skills for self-sufficiency, positive behaviours and independent attitudes towards disease. 3941…”
Section: Resultsmentioning
confidence: 99%
“…Details regarding design and outcome measures are described in the study protocol. 19 HRQoL, mental health, self-efficacy, and self-management outcomes were selected based on effects evidence from T2DM self-management intervention reviews and metaanalyses. [24][25][26] Trained research assistants obtained outcome data at baseline and 6 months after the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of a 6-month self-management program for community-dwelling older adults with T2DM and MCC was assessed in comparison to a control group receiving usual care. Details of the study design and outcomes are reported in the published study protocol [19].…”
Section: Methodsmentioning
confidence: 99%
“…Details regarding outcome measures are described in the study protocol [19]. The primary study outcome was the Physical Component Summary (PCS) score from the 12item Medical Outcomes Study Short Form-12v1 Health Survey (SF-12) [29].…”
Section: Outcomes and Measuresmentioning
confidence: 99%
See 1 more Smart Citation